14\(\dfrac{6}{7}\) : \(\left(\dfrac{4}{3}-\dfrac{5}{7}\right)\) + \(14\dfrac{6}{7}\) : \(\left(\dfrac{2}{3}-\dfrac{2}{7}\right)\)
= 14\(\dfrac{6}{7}\) : \(\dfrac{13}{21}\) + 14\(\dfrac{6}{7}\) : \(\dfrac{8}{21}\)
= 14\(\dfrac{6}{7}\) :\(\left(\dfrac{13}{21}+\dfrac{8}{21}\right)\)
= 14\(\dfrac{6}{7}\) : 1
= \(\dfrac{104}{7}\)
\(14\dfrac{6}{7}:\left(\dfrac{4}{3}-\dfrac{5}{7}\right)+14\dfrac{6}{7}:\left(\dfrac{2}{3}-\dfrac{2}{7}\right)\)
=\(14\dfrac{6}{7}:\left(\dfrac{13}{21}\right)+14\dfrac{6}{7}:\left(\dfrac{8}{21}\right)\)
=\(14\dfrac{6}{7}:\left(\dfrac{13}{21}+\dfrac{8}{21}\right)\)
=\(14\dfrac{6}{7}:1\)
=\(14\dfrac{6}{7}=\dfrac{104}{7}\)